Preventing Bullying through the Experimental Ta’awun Program among Boarding School Students - Fitriah M. Suud; Faisal Bin Husen Ismail; Mirawati Mirawati; Tri Na'imah; Anniez Rachmawati Musslifah; Shinta Shinta; Sholawati Sholawati; Mohd Shafiq Bin Sahimi (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
Prior research has demonstrated that bullying at Islamic boarding schools is a concerning issue, since it can hinder the psychological, social, and spiritual growth of students. Islamic boarding schools continue to report numerous incidents of bullying, encompassing verbal, physical, and social manifestations, despite their recognition as institutions that promote Islamic values. This study implemented a program to reduce bullying behaviour in a boarding school. This experimental study utilised both quantitative and qualitative methods, notably implementing a pretest-posttest design. Researchers selected a total of 30 students. The researchers gathered data by distributing a questionnaire designed to quantify the bullying variable. Following the data collection, the researchers implemented an intervention. Before the Ta'awun training intervention, researchers conducted a pretest to assess the students' baseline comprehension of bullying. Researchers utilised the pretest data to delineate the participants' status before the intervention. Researchers conducted a posttest in the last phase to evaluate the participants' knowledge of bullying following the intervention. The results indicated an 8.33% improvement in kids' comprehension of anti-bullying Ta'awun. The students successfully developed posters displaying the words